1998
DOI: 10.2337/diacare.21.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being and Symptoms in Relation to Insulin Therapy in Type 2 Diabetes

Abstract: Initiation of insulin therapy in type 2 diabetes improves glycemic control effectively, has little influence on physical and psychological well-being dimensions, and does not affect treatment satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 0 publications
1
54
0
1
Order By: Relevance
“…It should be noted that in three out of the four subgroups the baseline NA turned out to be significantly higher at the 1-month follow-up, irrespective of PA baseline levels and the course of PA change. The finding seems to confirm research reports about negative consequences of insulin therapy for diabetic patients' wellbeing (de Sonnaville et al, 1998;Goddjin et al, 1999), suggesting that they perceive the situation as difficult. On the other hand, it should not be overlooked that these negative changes were accompanied if not by at least moderate PA, then by its levels increasing over time.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It should be noted that in three out of the four subgroups the baseline NA turned out to be significantly higher at the 1-month follow-up, irrespective of PA baseline levels and the course of PA change. The finding seems to confirm research reports about negative consequences of insulin therapy for diabetic patients' wellbeing (de Sonnaville et al, 1998;Goddjin et al, 1999), suggesting that they perceive the situation as difficult. On the other hand, it should not be overlooked that these negative changes were accompanied if not by at least moderate PA, then by its levels increasing over time.…”
Section: Discussionsupporting
confidence: 80%
“…Some studies reported either no change in the patients' quality of life (de Grauw, van de Lisdonk, van Gerwen, van den Hoogen, & van Weel, 2001;UKPDS 37, 1999) or negative mood changes including problems with social functioning, greater emotional fatigue and perceived burdensomeness of the treatment (Goddjin et al, 1999;Reach, Le Pautremat, & Gupta, 2013;de Sonnaville et al, 1998), as well as increased tension, but only in patients with more frequent hypoglycemic episodes (UKPDS 37, 1999). Opposite effects were also noted, i.e.…”
mentioning
confidence: 99%
“…Some prospective studies suggest that the shift from a treatment consisting of exercise and/or tablets to insulin therapy can improve the glycaemic control of patients with Type 2 diabetes, without influencing their quality of life [5,6] or with even improving it [7]. In contrast, another study [8] has found that introduction of insulin therapy, initially had no effect on the quality of life of patients with Type 2 diabetes.…”
mentioning
confidence: 96%
“…In the health domain, the Profile of Moods States is frequently used to measure well-being (e.g., Chamove & Soeterick, 2006;Sonnaville et al, 1998;Van der Does et al, 1996), although well-being is best construed as the cumulative effect of a series of mood states. According to McNair, Lorr, and Droppleman (1992), moods are mild, pervasive, and generalized affective states that are perceived subjectively by individuals.…”
mentioning
confidence: 99%